Evaluation Of Anti-Aggressive Potential Of Aqueous Flowers Extract Of Hibiscus Rosa- Sinensis In Mice - Verma, Puspa; Dwivedi, Shruti; Lodhi, Omkar; Pal, Poonam (Journal of Neonatal Surgery, 2025)
The present study was on the evaluation of anti-aggressive potential of aqueous flowers extract of hibiscus rosa- sinensis in mice. The flowers extract of the Hibiscus rosa- sinensis were collected from Amsar Private Limited, Himanchal Pradesh. The flowers extract was identified by the Testing Chemist (S. Paliwal). Amsar Private Limited, Himanchal Pradesh. Swiss Albino mice (20-30g) of male and female of approximate 9–12-week-old were procured from animal house of Rameshwaram Institute of Technology and Management, Lucknow, Uttar Pradesh. The experimental protocol was approved by Institutional animal ethics committee (Registration no.-1397/ac/10CPCSEA). Preliminary phytochemical screening, UV, TLC, IR and NMR spectral analysis were done. The anti-aggressive potential was evaluated using various models i.e., Resident-intruder aggression, Water competition test, Forced swimming test and Open field test. Acute and sub-acute oral toxicity studies were done. Extract was given orally at two different dose levels (200 and 400 mg/kg) once daily for three consecutive days, while CMC (Carboxy Methyl Cellulose, 1%), Diazepam (1mg/kg), was administered as positive control. In results, Hibiscus rosa-sinensis (200 and 400 mg/kg) on all the models produced significant anti-aggressive effects such as a reduction in vocalizations along with lowering of leaping, running, rearing, and facing each other, increased latency time to first attack, reduced spout gaining frequency along with a reduction in time spent which was found to be statistically significant compared to the control. It concluded that both the doses of aqueous flowers extract of Hibiscus rosa- sinensis (200 and 400mg/kg) significantly reduced the immobility time. The observed effects of diazepam in this model were qualitatively like those of Hibiscus rosa- sinensis which is found data statistically significant (P<0.05, P<0.0001) compared to control.